Promotion of healthy lifestyle on the example of the problem of patella dislocation in athletes - Marosz, Szymon; Borkowska, Aleksandra; Biszewski, Mateusz; Marosz, Karol; Borkowska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction: Both in Poland and around the world, many people, especially those who regularly engage in sports, struggle with a wide variety of musculoskeletal ailments. One of them, relatively often occurring against the background of problems affecting the knee and patellofemoral joint, is the problem of patellar dislocations. Patellar dislocation is the slipping of the patella out of its proper place, which is the trochlea of the femur. The ailments mentioned above are of particular importance for athletes. To prevent this, any physical activity should be approached with care, and effective treatment and rehabilitation methods should be implemented. The aim of the study: The objective of the study was the presentation the case of a man dancer patient who experienced a dislocated patella during ballroom dance training and to present current methods of treatment and management of patellar dislocations in athletes based on a review of the PubMed and Google Scholar literature. Results: The case report concerns a 21-year-old patient who suffered a first-time injury of lateral dislocation of the patella of the right knee during ballroom dance training. The patient's symptoms included severe pain, swelling and complete limitation of mobility of the right knee. An X-ray confirmed a dislocation of the patella. Based on the examination performed and the clinical picture, a diagnosis was made and an attempt was made to reposition the dislocation and appropriate treatment was administered. Conclusions: Acute dislocation of the patella is most often caused by an injury sustained during physical or athletic activity. Management of acute patellar dislocation includes manual adjustment of the patella, checking the continuity of soft structures and possible surgical repair, and long-term rehabilitation, but it does not always disqualify from sports, even at a professional level, but nevertheless can significantly impede it.